Whole-Genome Resequencing of Xiangxi Cattle Identifies Genomic Diversity and Selection Signatures - Luo, Xiaoyu; Li, Jianbo; Xiao, Chentong; Sun, Luyang; Xiang, Weixuan; Chen, Ningbo; Lei, Chuzhao; Lei, Hong; Long, Yun; Long, Ting; Suolang, Quji; Yi, Kangle (Frontiers in Genetics, 2022)
Understanding the genetic diversity in Xiangxi cattle may facilitate our efforts toward further breeding programs. Here we compared 23 Xiangxi cattle with 78 published genomes of 6 worldwide representative breeds to characterize the genomic variations of Xiangxi cattle. Based on clustering models in population structure analysis, we displayed that Xiangxi cattle had a mutual genome ancestor with Chinese indicine, Indian indicine, and East Asian taurine. Population genetic diversity was analyzed by four methods (nucleotide diversity, inbreeding coefficient, linkage disequilibrium decay and runs of homozygosity), and we found that Xiangxi cattle had higher genomic diversity and weaker artificial selection than commercial breed cattle. Using four testing methods (θπ, CLR, FST, and XP-EHH), we explored positive selection regions harboring genes in Xiangxi cattle, which were related to reproduction, growth, meat quality, heat tolerance, and immune response. Our findings revealed the extent of sequence variation in Xiangxi cattle at the genome-wide level. All of our fruitful results can bring about a valuable genomic resource for genetic studies and breed protection in the future.